THE EFFECT OF WORK DISCIPLINE ON TEACHER PERFORMANCE AT SMK NEGERI 9 MAKASSAR - Pradani Muhiding, A. Ifta Audia Putri; Hasbiah, Siti; Ruma, Zainal; Kurniawan, Agung Widhi; Wardhana Haeruddin, Muh. Ilham (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Work discipline encompasses teachers' ability to adhere to professional standards, fulfill their responsibilities, and exhibit a strong work ethic. This research aims to investigate the impact of work discipline on teacher performance at SMK Negeri 9 Makassar. Quantitative data was collected through questionnaires distributed to a sample of 35 individuals. Data collection involved observation, interviews, and questionnaires, with data processing aided by SPSS 23. Descriptive analysis, validity testing, reliability testing, normality testing, linearity testing, simple linear regression analysis, and partial testing (t-test) were employed for data analysis. The findings reveal that the work discipline variable yielded a t-statistic value of 8.930, surpassing the t-table value of 0.3338, with a significant level of 0.000 less than 0.05. This indicates that the alternative hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected. Consequently, it can be concluded that work discipline exerts a positive and significant influence on teacher performance at SMK Negeri 9 Makassar.